DETECTION OF RECURRENT SOFT TISSUE SARCOMAS OF EXTREMITIES - G. V. Zinovyev; G. I. Gafton; E. A. Busko; A. V. Mishchenko; V. V. Gridasov; I. G. Gafton; Yu. V. Semiletova (Сибирский онкологический журнал, 2017)
Treatment of advanced soft tissue sarcoma (STS) has passed a difficult and long way of evolution from amputation surgery to complex limb-salvage interventions, but the problem of local recurrence is relevant today as 100 years ago. Tactics of monitoring after treatment of STS depends on the individual risk of recurrence and should be based on simple and effective diagnostic methods. Developing of new individualized approaches to patient follow up after primary treatment of STS is extremely necessary for early detection of local recurrence and improvement of overall survival, which requires close cooperation of clinical, morphological and radiology specialists.